Sosialisasi Peningkatan Pendapatan Rumah Tangga Kecamatan Talang Ubi Kabupaten Pali - Asmanita Asmanita; Henni Indriyani; Rolia Wahasusmiah; Darius Antoni (Jurnal Nasional Pengabdian Masyarakat, 2021)
The primary goal of Community Service (PKM) is to spread knowledge to the community surrounding the university where the professor is housed. Furthermore, the goal of Community Service (PKM) is to bring educational institutions closer to the community so that universities may help the government accelerate development activities and train high-quality development actors. Counseling and training are the goals of this Community Service (PKM) project in North Talang Ubi Village, Talang Ubi District, Penukal Abab Lematang Ilir Regency. In terms of socialization of growing household income, the goal is to raise public The primary goal of Community Service (PKM) is to spread knowledge to the community surrounding the university where the professor is housed. Furthermore, the goal of Community Service (PKM) is to bring educational institutions closer to the community so that universities may help the government accelerate development activities and train high-quality development actors. Counseling and training are the goals of this Community Service (PKM) project in Desa Talang Ubi Utara, Kecamatan Talang Ubi, Kabupaten Penukal Abab Lematang Ilir. In terms of the socialization of growing household income, the goal is to raise public awareness about how to increase household income and ensure that the benefits of this service are embraced by the residents of North Talang Ubi Village. With the socialization of increasing household income, the community can find out how to alternatively increase household income with the economic potential in the family. From the activities that have been carried out, several obstacles occur, including the low level of education, which impacts thinking patterns in overcoming problems of family economic constraints, lack of job opportunities/opportunities.